Effects of Acute Plasma Volume Expansion on Renal Perfusion, Filtration, and Oxygenation After Cardiac Surgery: A Randomized Study on Crystalloid vs Colloid. Issue 3 (June 2016) - Skytte Larsson, J.; Bragadottir, G.; Krumbholz, V.; Redfors, B.; Sellgren, J.; Ricksten, S.-E.
Abstract : (Abstracted from Br J Anaesth, 115:736–742, 2015) Researchers evaluated the differential effects of both colloid and crystalloid fluid retention on renal oxygen delivery, glomerular filtration, renal oxygen consumption, and the renal oxygen supply-demand relationship after cardiopulmonary bypass surgery. Subjects included 30 patients with normal preoperative renal function who underwent uncomplicated cardiac surgery.